2021
DOI: 10.3390/app11041582
|View full text |Cite
|
Sign up to set email alerts
|

Computer Tools to Analyze Lung CT Changes after Radiotherapy

Abstract: The paper describes a computer tool dedicated to the comprehensive analysis of lung changes in computed tomography (CT) images. The correlation between the dose delivered during radiotherapy and pulmonary fibrosis is offered as an example analysis. The input data, in DICOM (Digital Imaging and Communications in Medicine) format, is provided from CT images and dose distribution models of patients. The CT images are processed using convolution neural networks, and next, the selected slices go through the segment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…We have developed a dedicated server-based application described in [ 16 ] for study purposes. The workflow started with uploading CT images and RT-specific DICOM files (RT_dose, RT_structure) and automatically selecting lung-containing scans using artificial intelligence (neural network VGG16).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have developed a dedicated server-based application described in [ 16 ] for study purposes. The workflow started with uploading CT images and RT-specific DICOM files (RT_dose, RT_structure) and automatically selecting lung-containing scans using artificial intelligence (neural network VGG16).…”
Section: Methodsmentioning
confidence: 99%
“…Some authors showed a dose-response relation, evolution in time, and basic predictive factors [ 10 , 11 , 12 , 13 , 14 , 15 ]. There are few examples of dedicated software for big-data analysis of DICOM (Digital Imaging and Communications in Medicine) lung images [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The 3D affine registration method was employed to register the inhale and exhale CT images of the lung based on the lung segmentation conducted in the previous step as the image mask. More details on the 3D affine registration can be found elsewhere [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…The lung tissue density change expressed in Hounsfield Units (HU) derived from CT scans can be a numeric surrogate as it seems to fit the most commonly implemented NTCP models of lung response to radiation [ 33 ]. There are also some examples of dedicated software for big-data analysis of DICOM lung images [ 34 ].…”
Section: Quantitative Assessment Of Lung Density Changes After Radiot...mentioning
confidence: 99%